2009
DOI: 10.1007/s00348-009-0776-5
|View full text |Cite
|
Sign up to set email alerts
|

3D reconstruction of the flow and vortical field in a rotating sharp “U” turn channel

Abstract: Particle image velocimetry experiments have been carried out to obtain visualizations and measurements of the main and secondary flow fields in a square channel with a sharp ''U'' turn. Both the main and the secondary flow fields have been used to perform a 3D reconstruction of the mean flow and vortical fields in the turn region and in the outlet duct. In order to study the influence of the rotation, tests both in stationary (absence of rotation, Re = 20,000) and in rotating (Re = 20,000 and Ro = 0.3) conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The length of the primary separation bubble decreases monotonically with the increase of rotation on leading side. Gallo and Astarita [16], Sante and Braembussche [17] all investigated the mainstream field in rotating channels. Gallo performed a reconstruction and vertical field of the mainstream to study the influence of rotation by PIV.…”
Section: Effect Of Coriolis Force On Mainstreammentioning
confidence: 99%
“…The length of the primary separation bubble decreases monotonically with the increase of rotation on leading side. Gallo and Astarita [16], Sante and Braembussche [17] all investigated the mainstream field in rotating channels. Gallo performed a reconstruction and vertical field of the mainstream to study the influence of rotation by PIV.…”
Section: Effect Of Coriolis Force On Mainstreammentioning
confidence: 99%
“…For the rotating case, the distributions of the mean velocity components have been obtained adopting two different procedures for the yz-and xz-planes, whose detailed description is provided in a previous work of the same authors (Gallo and Astarita 2010). …”
Section: Piv Measurementsmentioning
confidence: 99%
“…It was found that the heat transfer was obviously enhanced at the point of fluid impact; at the same time, the heat transfer was also enhanced to a certain extent at the position where the vortex was generated. M.Gallo [13] et al also obtained the visualizations of the main and secondary flow fields in a U-shaped channel and perform a 3D reconstruction of the mean flow and vortical fields. J.Visscher [14] et al investigated the massively separated turbulent flows with rotation by PIV.…”
Section: Introductionmentioning
confidence: 99%